Barking up the wrong tree [large type] - McKinlay, Jenn (McKinlay, Jenn. Bluff Point romances., 2018)
Carly DeCusati returned home to Bluff Point, Maine, with her tail between her legs. But she's determined to get her life back on track--and that means finding new homes for the elderly golden retriever and overly talkative parrot she inherited before her old life fell apart. Enter physical therapist and hot one-night stand James Sinclair. James doesn't care that Carly doesn't do relationships. He is determined to win her heart, promising to help her with the pets if she'll just give him the time of day. Carly agrees to date the irresistible James, and, for the first time in years, she's dreaming of a happily ever after. But James has secrets, and if he can't open up to Carly, their future could go to the dogs.